PK-12 Virtual Schools: The Challenges and Roles of School Leaders - Jesus Abrego Jr.; Anita Pankake (Educational Considerations, 2010)
According to Jacobsen, Clifford and Friesen (2002), the expansion of instructional technology is due in part to an increase in demand by local communities to make sure that local schools are effectively preparing students for the technological challenges of the 21st century.
Keywords: PK-12 Virtual Schools; online learning; program; technology; students; 44 states; digital immigrants; digital natives; digital age; Long-Term Success